Relationships Between Measures of Functional and Isometric Lower Body Strength, Aerobic Capacity, Anaerobic Power, Sprint and Countermovement Jump Performance in Professional Soccer Players - Boraczyński, Michał (J Hum Kinet, 2020)
The purpose of this study was to assess a wide range of physiological and performance variables and investigate whether and to what extent these variables are associated with each other in soccer. Twenty-five male soccer players (25.1 ± 4.56 years; body mass, 75.2 ± 5.92 kg; body height, 180.6 ± 5.45 cm) performed: 5- and 30-m sprints (T5m and T30m, respectively), 1-repetition-maximum (1RM) half squat, maximal voluntary isometric contraction (MVIC) of the knee extensors, countermovement jump (CMJ) to obtain vertical jump height (CMJ(height)) and power output (CMJ(power)), the 10-s Wingate Anaerobic Test (WAnT) to obtain peak power (P(max)), and the 20-m multi-stage shuttle run test (MST) to evaluate aerobic capacity. 1RM, MVIC, and P(max) were normalized to body mass. Large negative correlations were found between sprint times and 1RM half back squat/BM (r = -0.510 to -0.570, r(2) = 0.260–0.325, both p < 0.01) and P(max)/BM (r = -0.501, r(2) = 0.251, p < 0.01). T30m most strongly and negatively correlated with CMJ(height) (r = -0.744, r(2) = 0.554, p < 0.001). WAnT-determined P(max) showed a very large correlation between absolute P(max) and knee-extensor MVIC (r = 0.827, r(2) = 0.684, p < 0.001) and large correlations between absolute P(max) and 1RM half squat (r = 0.674, r(2) = 0.454, p < 0.001) and CMJ(power) (r = 0.579, r(2) = 0.335, p < 0.01). We also identified a large inverse relationship between CMJ(height) and T30m (r = -0.744, r(2) = 0.554, p < 0.001) and large positive correlation between CMJ(height) and MVIC/BM (r = 0.702, p < 0.001). The results demonstrate that elite soccer players with greater lower body strength (quantified by the MVIC of the knee extensor and the 1RM half squat) show better sprint and CMJ performance, suggesting the incorporation of soccer-specific resistance training to develop lower body musculature and therefore maximize sprinting ability. The higher correlation coefficients found between T30m and the physiological and athletic measures compared with T5m promote the use of this sprint distance when assessing performance. The use of relative measures (normalized to body mass) is advisable when comparing strength variables with sprint and CMJ performance or anaerobic power. Considering the correlations of WAnT-determined P(max) versus CMJ(power), coaches should administer tests that assess jumping and linear sprint performance rather than the cycling-specific WAnT.